Factors Affecting Students' Spirituality - Simbolon, Pomarida; Simbolon, Nagoklan (Proceeding International Conference on Religion, Science and Education, 2025)
Spirituality is a person's belief in a greater power which is a source of strength for each individual so that it motivates individuals to get closer and creates love for themselves, others, God and the environment. The aim of the research was to determine the factors that influence student spirituality. The research design used in the research is an analytical design using a cross sectional approach. Sampling in this study used a simple random sampling technique with a sample size of 88 people. Data analysis using multiple logistic regression tests. The results of the research are factors that influence spirituality, namely one sub-variable that has the most influence on spirituality, namely the religious factor (p value=0.032<0.05). The religious factor has a B coefficient of 0.032 and an exp (B) of 3.9. This means that students with a religion factor of 3.9 times will have high spirituality. It is hoped that students will be able to increase their spirituality by being more self-reflective on the meaning of life, being able to have and adhere to their own beliefs which may be different from those of most people.